IMPORTANT FEATURES OF SOME WORDS IN ENGLISH AND UZBEK - Budikova Marguba Xoshimovna (Scholar Express Journals, 2022)
Choosing the concept of "property" as the subject of linguistic research, we could not leave out phraseological units and paremies in English and Uzbek, which are important for creating a holistic image of the object under consideration
Keywords: concept, phraseological units, paremiological units